2017
DOI: 10.1107/s2414314617006721
|View full text |Cite
|
Sign up to set email alerts
|

2,6-Dichloro-4-nitrotoluene

Abstract: The title compound, C7H5Cl2NO2[systematic name: 1,3-dichloro-2-methyl-5-nitrobenzene], crystallizes in the chiral space groupP212121with a Flack parameter of −0.03 (5). The methyl C atom, the Cl atoms and the N atom of the nitro substituent all lie extremely close to the plane of the benzene ring; the deviations are 0.028 (3) Å for the methyl C atom, −0.016 (1) and 0.007 (1) Å for the two Cl atoms, and −0.017 (3) Å for the nitro N atom. Hence, no significant steric hindrance of the methyl group by theorthohalo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 10 publications
1
5
0
Order By: Relevance
“…In DBNT (Medjroubi et al, 2016), there are two independent molecules per asymmetric unit and the methyl group H atoms are positionally disordered, as found for DBM (Hernandez et al, 2003). While in the compounds DINT and DCNT (Medjroubi et al, 2017), there is only one molecule in the asymmetric unit and no disorder is observed for the methyl group H atoms. In the molecule of DINT, a C m -H (m = methyl) bond is perpendicular to the mean plane of the molecule, as found for triiodomesitylene (TIM; Boudjada et al, 2001).…”
Section: Figurementioning
confidence: 58%
See 4 more Smart Citations
“…In DBNT (Medjroubi et al, 2016), there are two independent molecules per asymmetric unit and the methyl group H atoms are positionally disordered, as found for DBM (Hernandez et al, 2003). While in the compounds DINT and DCNT (Medjroubi et al, 2017), there is only one molecule in the asymmetric unit and no disorder is observed for the methyl group H atoms. In the molecule of DINT, a C m -H (m = methyl) bond is perpendicular to the mean plane of the molecule, as found for triiodomesitylene (TIM; Boudjada et al, 2001).…”
Section: Figurementioning
confidence: 58%
“…2. The structures of the title compounds are ISSN 2056-9890 compared with those of the dichloronitrotoluene (DCNT; Medjroubi et al, 2017) and dibromonitrotoluene (DBNT; Medjroubi et al, 2016) analogues, illustrated in Fig. 3.…”
Section: Structural Commentarymentioning
confidence: 99%
See 3 more Smart Citations